Rare Variants of Dermatofibrosarcoma Protuberans: Clinical, Histologic, and Molecular Features and Diagnostic Pitfalls - Celestine M. Trinidad; Sintawat Wangsiricharoen; Victor G. Prieto; Phyu P. Aung (Dermatopathology, 2023)
Dermatofibrosarcoma protuberans (DFSP) is a dermal malignant mesenchymal tumor. Most variants are associated with a high risk of local recurrence and a low risk of metastasis. The classic histomorphology of this tumor is made up of uniform, spindle-shaped cells, arranged in a storiform pattern. Tumor cells characteristically infiltrate the underlying subcutis in a honeycomb pattern. Less common variants of DFSP have been identified: myxoid, pigmented, myoid, granular cell, sclerosing, atrophic, and fibrosarcomatous. Only the fibrosarcomatous variant has been shown to differ significantly from classic DFSP in terms of clinical outcome; fibrosarcomatous DFSP has been shown to be associated with a greater risk of local recurrence and metastatic potential than classic DFSP. However, the other variants may pose diagnostic difficulty as they resemble other types of spindle cell neoplasms, especially in small biopsy specimens. This article reviews the clinical, histologic, and molecular features of DFSP variants, as well as possible pitfalls in their diagnosis and how to resolve them.